Securing Annulus Abnormal Pressure Build-up (APB) with Polymer Plug; a Case Study - Ganesha R Darmawan (Journal of Petroleum and Geothermal Technology, 2020)
The life cycle of a production well was facing challenges related to well integrity issue where A-Annulus pressure tracking the tubing pressure and increased repeatedly above the Maximum Allowable Wellhead Operating Pressure (MAWOP). Several well control operations were executed to reduce A-Annulus abnormal pressure build-up (APB) with no success.Literature and well historical studies were performed in order to secure this well, normal bleed and lube was ruled out owing to several attempts already performed for more than a year, but the APB keep on appearing after 2-4 months. Bullheading is not a viable option to kill the well. Well securing planned and prepared with some options such as, mechanical barriers/plugs, cement plug or polymer plugs as temporary plug to avoid APB re-occurrence. There were some constrains in operation planning that need to be addressed carefully, with additional challenge of tight injectivity as if it was a closed system.The polymer plug successfully stops the gas migration to surface, and secured the well from any reoccurrences of APB. The details of well control histories, operation design and planning and operation execution with the complete results and evaluation will be presented in this paper.